2010
DOI: 10.1155/2010/326736
|View full text |Cite
|
Sign up to set email alerts
|

Internal Friction on AISI 304 Stainless Steels with Low Tensile Deformations at Temperatures between50 and 20C

Abstract: Austenitic stainless steels specimens were deformed by tension in temperatures in the range of −50 • C to 20 • C and 0.03 to 0.12 true strain, in order to obtain different volumetric fractions of ε (hexagonal close packed) and α (body centered cubic) strain induced martensites. The morphology, distribution and volumetric fractions of the martensites were characterized by metallography and dilatometry analysis and quantified by ferrite detector measurements. The damping behavior of specimens with different volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…α 0 , ε-martensite can act as an intermediate phase during the transformation of γ into α 0 . [38,47,[51][52][53] Studies done by Guo et al [32] , Soares et al, [39] and De et al [50] revealed that the reduction in the work hardening rate decay can be associated with α 0 -martensite formation in the microstructure with the progress of deformation. Therefore, in stage II, the deformation-induced phase transformation is probably the mechanism responsible for the hardening of the material.…”
Section: Strain Hardening Behaviormentioning
confidence: 99%
“…α 0 , ε-martensite can act as an intermediate phase during the transformation of γ into α 0 . [38,47,[51][52][53] Studies done by Guo et al [32] , Soares et al, [39] and De et al [50] revealed that the reduction in the work hardening rate decay can be associated with α 0 -martensite formation in the microstructure with the progress of deformation. Therefore, in stage II, the deformation-induced phase transformation is probably the mechanism responsible for the hardening of the material.…”
Section: Strain Hardening Behaviormentioning
confidence: 99%
“…3. Metallographic analysis of longitudinal cross-section of the specimen in initial state after chemical etching in HNO 3 +HF+glycerine solution showed that the structure is non-homogeneous and have polyedric austenite grains with different grain sizes and occurrence of annealing twins and deformation martensite after plastic deformation as a result from the final treatment. In the case of AISI 316Ti titanium carbides TiC where present in the structure.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…The internal damping can be defined as the capacity of a material to damp mechanical vibrations. The capacity change of material to damp mechanical vibrations as function of time or temperature corresponds to a structural, microstructural and substructural change [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Uma microestrutura formada por frações aproximadamente iguais de ferrita e austenita proporciona aos AIDs alta resistência ao trincamento por corrosão-sob-tensão, corrosão localizada e uma resistência mecânica superior a dos aços inoxidáveis austeníticos convencionais (AIA), combinada a uma boa tenacidade [22]. Embora, os AIAs continuem sendo objeto de continuados estudos devido a sua conformabilidade, uma das mais demandadas propriedades deste tipo de aço em aplicações industriais [23,24].…”
Section: Soldagem De Aços Inoxidáveis Duplexunclassified